2005
DOI: 10.1007/s10935-005-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Student Outcomes of a Violence Prevention Curriculum

Abstract: Violence in schools and its prevention have become focal points for research, practice, and policy. This study investigated the effectiveness of the Second Step violence prevention curriculum on all fourth and fifth grade students (N = 455) in one small urban school district. Scores on tests measuring knowledge of the curriculum increased significantly. Significant positive changes were also found for Behavior Assessment System for Children items reflecting student use of problem solving as well as report card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 24 publications
0
31
0
1
Order By: Relevance
“…Forty-eight percent of the studies used two types of outcome measures, 22.6% of the studies used three types of outcomes, and 29% of the studies used only one type of measure. All but one study (Edwards et al 2005) reported a behavioral measure of involvement in bullying/victimization as an outcome measure. Researchers used a wide variety of different surveys to measure involvement in bullying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-eight percent of the studies used two types of outcome measures, 22.6% of the studies used three types of outcomes, and 29% of the studies used only one type of measure. All but one study (Edwards et al 2005) reported a behavioral measure of involvement in bullying/victimization as an outcome measure. Researchers used a wide variety of different surveys to measure involvement in bullying.…”
Section: Discussionmentioning
confidence: 99%
“…In the Heydenberk et al (2006) study, open-ended questions administered to teachers were used to gain additional data on program effectiveness and changes in student behavior. Edwards et al (2005) used open-ended, semi-structured interviews with students to collect data on the acceptability and impact of the Second Step program. Jennifer and Shaughnessy (2005) collected qualitative data using multiple sources and multiple methods, for example, semi-structured interviews with pupils, managers, and facilitators; observations of several aspects of school life; and facilitator diaries.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Edwards, Hunt, Meyers, Grogg, and Jarrett (2005) interviewed fourth and fifth grade students in an urban school district where Second Step was implemented. Eleven percent of the students reported that they either did not learn or chose not to use the skills in real-life situations.…”
mentioning
confidence: 99%
“…They did not, however, indicate the effectiveness of the skills or discuss the extent to which they used other skills targeted by the intervention. Edwards et al (2005) conducted open-ended interviews in which they asked fourth and fifth grade students who participated in Second…”
mentioning
confidence: 99%
“…(See www.cfchildren.org/programs/ssp/overview/ for a review of Second Step and related contemporary scholarship.) Contemporary research examining the efficacy of Second Step suggests that students' exhibit lowered levels of aggression (e.g., McMahon & Washburn, 2003) and increased levels of prosocial skills and behaviors (e.g., Edwards, Hunt, Meyers, Grogg, & Jarrett, 2005;Frey, Nolen, Edstrom, & Hirschstein, 2005;McMahon, Washburn, Felix, Yakin, & Childrey, 2000) after receiving instruction.…”
Section: Large-group Social Skills Instructionmentioning
confidence: 99%